Pengaruh Komunikasi Internal, Kepuasan Kerja, Motivasi dan Lingkungan Kerja terhadap Kinerja Guru (Business and Accounting Education Journal, 2022)
The purpose of this study was to analyze the effect of internal communication, job satisfaction, motivation, and work environment on teacher performance. The population is 74 teachers at SMK Negeri 2 Temanggung. This quantitative study uses a causality design. Sampling technique using saturated samples. Data were collected by questionnaire. Data were analyzed using descriptive percentage analysis and multiple linear regression analysis. The results showed that (1) simultaneously internal communication, job satisfaction, motivation, and work environment had an effect on performance by 56.6%, (2) partially there was a positive and significant influence on internal communication, job satisfaction, motivation and work environment on teacher performance at SMK Negeri 2 Temanggung. Internal communication affects performance by 12.46%, job satisfaction affects performance by 1%, motivation affects performance by 16.32%, and work environment affects performance by 12.67%.